ATP and Mg2+ promote the reversible oligomerization and aggregation of chloroplast 2-Cys peroxiredoxin - Aran, M. (2011)
2-Cys peroxiredoxins (2-Cys Prxs) are ubiquitous peroxidases with important roles in cellular antioxidant defense and hydrogen peroxide-mediated signaling. Post-translational modifications of conserved cysteines cause the transition from low to high molecular weight oligomers, triggering the functional change from peroxidase to molecular chaperone. However, it remains unclear how non-covalent interactions of 2-Cys Prx with metabolites modulate the quaternary structure. Here, we disclose that ATP and Mg2+ (ATP/Mg) promote the self-polymerization of chloroplast 2-Cys Prx (polypeptide 23.5 kDa) into soluble higher order assemblies (>2 MDa) that proceed to insoluble aggregates beyond 5mMATP. Remarkably, the withdrawal of ATP or Mg2+ brings soluble oligomers and insoluble aggregates back to the native conformation without compromising the associated functions. As confirmed by transmission electron microscopy, ATP/Mg drive the toroid-like decamers (diameter 13 nm) to the formation of large sphere-like particles (diameter ∼30 nm). Circular dichroism studies on ATP-labeled 2-Cys Prx reveal that ATP/Mg enhance the proportion of β-sheets with the concurrent decrease in the content of α-helices. In line with this observation, the formation of insoluble aggregates is strongly prevented by 2,2,2-trifluoroethanol, a cosolvent employed to induce α-helical conformations. We further find that the response of self-polymerization to ATP/Mg departs abruptly from that of the associated peroxidase and chaperone activities when two highly conserved residues, Arg129 and Arg152, are mutated. Collectively, our data uncover that non-covalent interactions of ATP/Mg with 2-Cys Prx modulate dynamically the quaternary structure, thereby coupling the non-redox chemistry of cell energy with redox transformations at cysteine residues. © 2011 by The American Society for Biochemistry and Molecular Biology, Inc.